Spillover effects in the nexus of finance-institutions-growth: New insights from spatial Durbin analysis on emerging economies - Ahmad, Mahyudin; Hall, Stephen G.; Law, Siong Hook; Nayan, Sabri (John Wiley and Sons Ltd, 2025)
Despite extensive finance-growth literature, the critical role of spatial interdependence between countries has often been overlooked. This paper addresses this gap by utilising spatial Durbin modelling on a 30-year panel dataset of 56 emerging economies, examining the spillover effects of financial development (FD) and institutions on economic growth. The findings reveal FD has a significant positive within-country impact on growth; on average, FD is expected to raise growth by approximately 5.8% holding other factors constant. Meanwhile, the FD spillover effect on growth is estimated to be around 10 times its within-country effect, which is not surprising given that the 10-nearest-neighbour is the preferred matrix for conceptualising the spatial dependence between the countries under study. The results however show no evidence of significant threshold effect of FD. Political institutions emerge as the most influential in driving growth both within and across countries, whereas improvement in economic institutions moderates the growth-effect of FD. FD's within-country effect on growth is largely driven by financial institutions, while its spillover effect stems primarily from the neighbours' financial markets. The findings' robustness is confirmed through a battery of tests. In conclusion, this study offers valuable insights into the complex finance-institutions-growth nexus in emerging economies. By considering spatial interdependencies and the role of institutions, policymakers can craft effective strategies to harness FD's positive effects and foster an environment for sustained, inclusive economic growth.